The Hague Protocol on the Law Applicable to Maintenance Obligations – the Latest Legal Source of Serbian Private International Law - Đundić, Petar; Bordaš, Bernadet (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
In January 2013 the National Assembly of Republic of Serbia has ratified the Protocol on the Law Applicable to Maintenance Obligations, adopted in 2007 by the Hague Conference on Private International Law. The Protocol represents a significant novelty in Serbian Private International Law since it introduces a comprehensive choice of law mechanism aimed at designating the law applicable to maintenance obligations between relatives. The article offers a review of the most important provisions of this source. The general rule of the Protocol is based on the application of the law in force at the debtor’s habitual residence. However, in vast number of cases there are derogations from the main principle in favor of application of the law of the forum. Unlike the Hague Convention on the Law Applicable to Maintenance Obligations (1973), which it replaces, the Protocol does not connect the maintenance obligations between ex spouses to the law applied to their divorce. Instead, it includes a special rule in art. 5 by which the law of the creditor’s habitual residence governs the maintenance obligations between spouses and ex spouses, with the possible derogation in favor of the law more closely connected with the marriage. Important place in the choice of law system is given to party autonomy. The article concentrates particularly on this aspect of the Protocol.